SAT0162 Complexes of anti-CRP autoantibodies and CRP-opsonised apoptotic cell remnants form a pro-inflammatory pathogen in systemic lupus erythematosus. (23rd January 2014) - Janko, C.; Pauthner, M.; Munoz, L.; Franz, S.; Schorn, C.; Sheriff, A.; Schett, G.; Herrmann, M.
Abstract : Background: An efficient clearance of dying and dead cells is essential to avoid inflammation and autoimmunity. Therefore, a plethora of opsonizing molecules secures silent clearance [1]. Opsonisation with C-reactive protein (CRP) of late apoptotic and necrotic cells serves as backup mechanism for cells which have escaped early clearance mechanisms. In Systemic Lupus Erythematosus a defective clearance leads to the induction of immune responses against several autoantigens and opsonins as CRP [2]. Objectives: The aim of this study was to analyse the particular contribution of anti-CRP autoantibodies to inflammation in conditions of autoimmunity. Methods: We analysed several cohorts of patients with Systemic Lupus Erythematosus and Anti-phospholipid syndrome from various European autoimmunity centers for the presence of anti-CRP IgG autoantibodies with ELISA. Healthy blood donors and patients with rheumatoid arthritis served as controls. Phagocytosis assays of CRP/anti-CRP sensitized secondary necrotic cells by macrophages were performed and cytokine release analysed to identify contribution of anti-CRP autoantibodies in inflammation. Results: We confirm the presence of anti-CRP IgG autoantibodies in patients with Systemic Lupus Erythematosus and Antiphospholipid syndrome. We observed both CRP and anti-CRP autoantibodies bound to the surfaces of secondary necrotic cells and being accessible for phagocytic effector cells. Opsonization with CRP of secondary necrotic cells did neither affect phagocytosis nor the cytokine response profile. However, sensibilisation of CRP-opsonized secondary necrotic cells with anti-CRP IgG provokes a more inflammatory cytokine response. Conclusions: In conclusion, anti-CRP, CRP and secondary necrotic cells form a ternary pyrogen endowed with strong pro-inflammatory capabilities which are able to maintain and perpetuate chronic inflammation. Anti-CRP-IgG is a further example of the proinflammatory family of anti-opsonine autoantibodies. References: Ravichandran KS. Beginnings of a good apoptotic meal: the find-me and eat-me signaling pathways. Immunity. 2011, 28;35:445-55. Sjöwall C, Zickert A, Skogh T, Wetterö J, Gunnarsson I. Serum levels of autoantibodies against C-reactive protein correlate with renal disease activity and response to therapy in lupus nephritis. Arthritis Res Ther. 2009;11:R188. Disclosure of Interest: None Declared